7S-McKinsey Based Organizational Performance Model on MSMEs - Choirul Anam; Madziatul Churiyah (Universitas Islam Kadiri, 2023)
In facing economic challenges and global competition, applying this organizational performance model can help MSMEs increase business effectiveness. This examine discusses making use of the organizational performance model primarily based on the 7S-McKinsey framework to MSME organizations. This study objectives to recognize the effectiveness of the 7S-McKinsey organizational performance model in improving the overall performance of MSMEs. This studies makes use of a qualitative technique to descriptive techniques. records series includes interviews, observations, and documentation. 7S-Mckinsey mapping as data analysis to determine the strategy, structure, capabilities, styles, staff, systems, and shared values contained in MSMEs. The goal is to be able to find out the mapping7S-McKinsey found in MSMEs. The results showed that applying an organizational performance model based on the 7S-McKinsey framework can improve the performance of MSMEs. In this case, the essential elements are strategy, structure, and capabilities, followed by elements of standard style, staff, system, and values. This research contributes practically to the importance of understanding the effectiveness of the 7S-McKinsey organizational performance model to improve MSME performance.